PENINGKATAN HASIL BELAJAR DI MASA PANDEMI DENGAN MENGGUNAKAN LEMBAR KERJA PESERTA DIDIK BERORIENTASI KETERAMPILAN PROSES SAINS - Mirza Roma Apsari; Mohammad Budiyanto (PENSA: E-JURNAL PENDIDIKAN SAINS, 2021)
This study aims to describe the improvement of student learning outcomes by using scientific skill process on student worksheet. The research design uses in this study was One Group Pretest-Posttest Design. This research is test to student on IX class at JHS 3 Tuban with total 32 students in one class. The data collection method uses in this research is the test method. The knowledge test is pretest to determine the initial ability of student and posttest to determine the final ability of student after being given treatment. The skill test is in the form of integrated scientific skill process in terms of 7 aspects. The learning outcomes of knowledge are classified as medium N-Gain, namely 0,36. The learning outcomes of knowledge are obtained by 24 students who experinced an increase in learning outcomes, 5 students did not change learning outcomes, and 3 students experinced a decrease in learning outcomes. Learning outcomes of integrated scientific skill process show better result than learning outcomes of knowledge. Learning outcomes of integrated scientific skill process, namely 85,04 are included in the very good criteria. This is due to the enthusiasm and motivation of student when participating in practical learning. The conclusion of this study is scientific skill process on student worksheet is able to improve learning outcomes in the knowledge dimension and learning outcomes in the dimensions of integrated scientific skill process.